Rancang Bangun Media Pembelajaran bagi Murid Sekolah Menengah Pertama Luar Biasa (SMPLB) 1 Palangka Raya - Putu Bagus Adidyana Anugrah Putra; Viktor Handrianus Pranatawijaya; Admi Ruth Sinana (Anterior Jurnal, 2018)
Science and technology are growing very rapidly, one of them in the field of web applications that is growing rapidly because of internet technology. Web-based applications can be used as learning media. Learning media as a tool to improve the quality of education is very important in the learning process. In this research, Sekolah Luar Biasa Negeri 1 Palangka Raya, especially at the level of the Junior High School (SMPLB) was used as a reference in making learning media. Students at SMPLB are students with special needs. This learning media application is intended for students who deficient in the sense of hearing and speaking. This website-based learning media application was developed using the waterfall method with the stages of system analysis, such as the acquisition of data requirements, technology used in business processes and activity plans. Data Flow Diagrams (DFD) and Entity Relationship Diagrams (ERD) are also used in this application. Table design is used in this application, while navigation design uses a sitemap. Interface design and implementation are done with the PHP programming language. In the testing phase using black-box testing. This learning media is an additional teaching material where the visual side of the students can be used to directly see the learning object.